PENGARUH PEMBERIAN MAKANAN TAMBAHAN TERHADAP STATUS GIZI, STATUS ANEMIA DAN PRESTASI AKADEMIK PADA MAHASISWA TINGKAT PERSIAPAN BERSAMA IPB T AHUN 2005/2006 - Budi Setiawan; Dodik Briawan; Rizal Damanik; Tjahja Muhamdri; Dias Indrasti (Media Gizi dan Keluarga, 2007)
Supplementary feeding program for needy student was designed to supplement target group's daily normal diet with the type of food nuded to alleviate their nutritional deficits. The location of the program was at the male and female students' dormitory of IPB Campus in Darmaga Bogor. The implementation of the program was started in November 2005 until June 2006. The result showed that the average of energy and protein intake of program participant increased significantly after the completion of the program. Accordingly, the prevalence of anemia in female students decreased while in male students the prevalence was constant. Moreover. average of serum ferritin of females increased while serum ferritin of males remained constant. After completion of the program, the number of underweight students decreased The number of female and male students who were shiftingfrom underweight to normal category was increased. Nutrition knowledge of students participant were categorized as good Academic performance (GPA) of student participants (3.01) indicated higher than non-participant (2.85).